Bias Gender dalam Berita Penangkapan Ahed Tamimi oleh Tentara Israel - Betty Ayunda Wulandari; Rihaadatul 'Aisy AlQodri; Mohammad Hotibul Umam; Abdul Muntaqim Al-Anshory (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
News about women's cases is often encountered both in online and print media. The purpose of this study was to examine the gender bias contained in the news of Ahed Tamimi's arrest by Israeli troops in online news TribunJatim.com and TribunJateng.com and what forms of framing exist in it. This research included descriptive qualitative research using Sara Mills' critical discourse analysis study. Online media TribunJatim.com and TribunJateng.com were the subject of this study, and online news articles revealing the case of Ahed Tamimi's arrest as the object of research. The results of this study show that, First, articles in online media TribunJatim.com and TribunJateng.com place the victim as an object by not providing space for the victim to tell the chronology of events through his point of view. Second, the author gives a more complete identity to male characters than females. Third, the author is more exposed from the point of Ahed's guilt without considering from the side of the Israeli army.